Understanding brands (Video Education Australasia, 2010)
"This engaging Australian-made program looks at what a brand is, the power of branding, what makes up a brand, the evolution of brands, and influences on brands. It also features Erminio Putignano from Futurebrand, who highlights some great examples of successful branding."--in container.